Review of the Geology of the Arun-Tamor Region, Eastern Nepal: Present Understandings, Controversies and Research Gaps - Adhikari, Drona; Silwal, Champak Babu; Paudel, Lalu Prasad (Journal of Institute of Science and Technology, 2021)
Systematic study of the eastern Nepal Himalaya was started after 1950 when Nepal opened up for foreigners. Thereafter, several geological studies have been carried out in the Arun-Tamor region of eastern Nepal Himalaya. The Tibetan-Tethys sedimentary sequence, the Higher Himalayan amphibolite to granulite facies metamorphic crystalline sequence, the Lesser Himalayan sedimentary and greenschist facies metasedimentary sequences, and the Siwalik foreland molassic sedimentary sequence are the four major tectonic units of this area. The individual nomenclature schemes of stratigraphic units, the correlational dispute, the positions and interpretations of regional geological structures are some examples that have created controversies regarding the lithostratigraphy and structural arrangements. The difference in age and genesis of the Main Central Thrust and its effects in the metamorphism of the eastern Nepal Himalaya are the exemplification of the contradiction in the interpretation of the tectonometamorphic history. There is a gap in research in the tectonics and episodic metamorphic evolution of the area owing to the bare approach in the microstructural and geochronological investigation. Future investigations should be focused on solving the above mentioned controversies and narrowing down the research gaps in tectonic and metamorphic evolution.